Adaptasi Organisasi Dalam Menghadapi Kemajuan Teknologi di Era Digital - Rofi', Muhammad Ahsanur; Adib, Mohammad (Department of Anthropology, 2024)
This research aims to analyse the adaptation efforts of the Culture Division Office in facing technological advances in the digital era. This research is analysed using Denison's organisational culture adaptation theory with three indices: creating change, customer focus, and organisational learning. This research method is descriptive qualitative with a case study approach. Data collection was conducted through interviews, observation, and documentation. Data analysis was carried out by collecting data, classifying, reducing, presenting data, and drawing conclusions. This research was conducted at the Office of the Culture Division of the Gresik Regency Disparekrafbudpora. The subjects of this research are the head of the culture division, young cultural advisor, language and literature analyst staff, and cultural heritage and museum analyst staff. The results of this study found that a) In terms of creating change, the cultural division office adapts by creating cultural heritage barcode innovations, utilising Instagram social media for promotional media, and utilising the OSS System; b) In terms of focusing on the community, the cultural division office adapts by utilising website platforms, social media, official numbers, and email as a means of receiving criticism and suggestions; dan c) In terms of organisational learning, the cultural division office adapts by creating a Virtual Museum, utilising the Zoom Platform, and implementing technical guidance programs.Abstrak: Penelitian ini bertujuan untuk menganalisis upaya adaptasi Kantor Bidang Kebudayaan dalam menghadapi kemajuan teknologi di era digital. Penelitian ini dianalisis menggunakan teori adaptasi budaya organisasi dari Denison, dengan tiga indeks yaitu menciptakan perubahan, fokus pada pelanggan, dan pembelajaran organisasi. Metode penelitian ini yaitu deskriptif kualitatif dengan pendekatan studi kasus. Pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi. Analisis data dilakukan dengan mengumpulkan data, mengklasifisikasi, mereduksi, menyajikan data, dan menarik kesimpulan. Penelitian ini dilakukan di Kantor Bidang Kebudayaan Disparekrafbudpora Kabupaten Gresik. Subjek penelitian ini yaitu kepala bidang kebudayaan, pamong budaya ahli muda, staf analis bahasa dan sastra, dan staf analis cagar budaya dan museum. Hasil penelitian menunjukkan bahwa: a) Dalam hal menciptakan perubahan, kantor bidang kebudayaan beradaptasi dengan membuat inovasi barcode cagar budaya, memanfaatkan media sosial Instagram untuk media promosi, dan memanfaatkan Sistem OSS; b) Dalam hal berfokus pada masyarakat, kantor bidang kebudayaan beradaptasi dengan memanfaatkan platform website, media sosial, nomor dinas, dan email sebagai sarana untuk menerima kritik dan saran; c) Dalam hal pembelajaran organisasi, kantor bidang kebudayaan beradaptasi dengan menciptakan Museum Virtual, memanfaatkan Platform Zoom, dan melaksanakan program bimtek.